KBB Acilleri - Erdemes, Servet; Özkara, Samira; Onur, Fırat; Mutaf, Mert; Tulğar, Meltem; Tarhan, Ceyda; Akbaş, Ali; Kınal, M. Emrah; Sizer, Bilal; Aliyeva, Aynur; Kavak, Ömer Tarık; Gündoğdu, Yavuz; et al. (Academician Publishing Book DOI Portal, 2023)
-